St. Jude Trifecta Versus Carpentier-Edwards Perimount Magna valves for the treatment of aortic stenosis: comparison of early Doppler-Echocardiography and hemodynamic performance - Minardi, Giovanni; Pergolini, Amedeo; Zampi, Giordano; Pulignano, Giovanni; Pero, Gaetano; Sbaraglia, Fabio; Pino, Paolo Giuseppe; Cioffi, Giovanni; Musumeci, Francesco (Monaldi Archives for Chest Disease, 2015)
Objective. Aim of this study was to compare the hemodynamic profiles of 2 aortic valve bioprostheses: the Carpentier Edwards Perimount Magna (CEPM) valve and the Trifecta valve. Methods. 100 patients who underwent AVR for severe symptomatic AS between September 2011 and October 2012 were analyzed by means of standard trans-thoracic Doppler-echocardiography. Results. Mean and peak gradients were significantly lower for the 21 mm Trifecta vs CEPM (11 ± 4 vs 15 ± 4 mmHg, and 20 ± 6 vs 26 ± 7 mmHg, respectively; all p < 0.05) and the 23 mm Trifecta vs CEPM (8 ± 2 vs 14 ± 4 mmHg, and 17 ± 6 vs 25 ± 9 mmHg; all p < 0.05). Effective orifice area tended to be slightly higher for the Trifecta valve. Conclusion. The new bioprosthetic valve Trifecta has an excellent hemodynamic profile, and lower trans-prosthesic gradients when compared to CEPM valve.